Islamic Education in the Age of Artificial Intelligence Policy Responses to Digital Transformation and Teacher Competency Challenges - Kholil Syamsul; Abd. Muis (DAAR EL-MAKRIFAH: Journal of Islamic Religious Education, 2026)
This study examines Islamic education in the age of Artificial Intelligence (AI) by focusing on policy responses to digital transformation and teacher competency challenges. The research aims to explore how Islamic educational institutions formulate and implement digital transformation policies, identify the challenges faced by Islamic Education teachers in developing professional, pedagogical, and digital competencies, and analyze the influence of these factors on the quality and sustainability of Islamic education. This study employed a qualitative case study approach conducted at an Islamic educational institution. Data were collected through interviews, observations, and documentation and analyzed using data condensation, data reduction, data display, and conclusion drawing. The trustworthiness of the findings was ensured through source triangulation, technique triangulation, and member checking. The findings reveal that Islamic educational institutions have implemented digital transformation policies through curriculum adaptation, technology integration, teacher training programs, and the utilization of AI-supported educational tools. However, teachers face challenges related to digital literacy, pedagogical adaptation, professional development, and the ethical use of AI. The study also found that digital transformation policies and teacher competency development significantly contribute to improving educational quality, student engagement, institutional effectiveness, and the long-term sustainability of Islamic education. The study concludes that successful adaptation to the AI era requires the integration of strategic policy frameworks, continuous teacher competency development, technological innovation, and value-based educational governance.